“We Came to a Village...”: Value Systems in a Changing World - Gyökér, Róbert (Ethnographica et Folkloristica Carpathica, 2022)
Although we experience an increasing level of cultural foreign experience in our time intensified by the pressure of migration and the development of information technologies, the conventional view of value systems still prevails in modern nations. Change in culture is a never-ending process, though. The persuasive power of stability and uniformity seems to decline in postmodernity transforming the role of nation states, as well. Peripheries and “partial truth” come into view. Value systems are also affected by these changes. Value systems are no longer cast from a single mold, but rather derive from a dynamically changing framework that is shaped by the dialogistic connection of the elements of the sociocultural realm, the central role of the subject’s interpretation and the positioned meaning of values. This paper attempts to describe the changes brought about by postmodernity through the everyday life of four families settled down in Hosszúhetény. After having embraced traditional values at a certain point in their life as a result of a conscious decision, families are compelled to reevaluate their former worldview. This process results in the revision of their identity, as well. In the end, they are trying to establish themselves through various representational practices in a village that has already been modernized. While trying to analyze the components of their value system, I define so-called correlations in the hope of realizing a more relevant understanding of the postmodern age.